2019
DOI: 10.1021/acs.macromol.9b00792
|View full text |Cite
|
Sign up to set email alerts
|

Small Change, Big Impact: The Shape of Precursor Polymers Governs Poly-p-phenylene Synthesis

Abstract: The synthesis of unsubstituted, structurally perfect poly(para-phenylene) (PPP) has remained elusive for many decades. By modifying our previously reported precursor route towards PPP, we were able to simplify and optimize the precursor polymer synthesis and yields, the thermal conversion process to PPP, and the resulting material properties. We describe the synthesis of unprecedented anti-dialkoxycyclohexadienylenes, polymerized via Suzuki coupling to yield linear PPP precursor polymers. Changing the geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Since the same emission spectra were obtained, regardless of the geometry of the precursor, we conclude that the different optical properties of the polymers (see Supporting Information, Figure S7), which emit at 485, 520 and 560 nm for PPP anti and 426, 450, 485 and 560 nm for PPP syn , respectively, are a consequence of their differing morphologies and solid‐state order. Furthermore, the estimated timescales of the aromatization process for both isomers are comparable to each other and with that of PPP anti (5 min) and much faster than that of PPP syn (40 min) [2, 3] …”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Since the same emission spectra were obtained, regardless of the geometry of the precursor, we conclude that the different optical properties of the polymers (see Supporting Information, Figure S7), which emit at 485, 520 and 560 nm for PPP anti and 426, 450, 485 and 560 nm for PPP syn , respectively, are a consequence of their differing morphologies and solid‐state order. Furthermore, the estimated timescales of the aromatization process for both isomers are comparable to each other and with that of PPP anti (5 min) and much faster than that of PPP syn (40 min) [2, 3] …”
Section: Resultsmentioning
confidence: 54%
“…The easily evaporable methoxy‐masked para ‐terphenyl makes the use of a sealing‐tube indispensable, in which the leaving‐groups (formally methoxy radicals) are trapped in the vessel and might cause additional side‐reactions. In contrast, no rearrangements were observed for our precursor polymer thin films (Scheme 1 d and e), in which dialkoxylated cyclohexadienylene moieties were thermally aromatized under nitrogen atmosphere and ambient pressure [1–3] . We concluded that aromatization was far more selective in thin films: the precursor polymers PPP syn,pre and PPP anti,pre did not melt in contrast to methoxy‐masked para ‐terphenyl (cf.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations